WANA TANI SEBAGAI SALAH SATU METODE DALAM KONSERVASI TANAH DAN AIR - Satriawan, Yohanes Emil (Agriculture Faculty of Flores University, 2008)
Soil and water are the most important resources. Soil is the main media for people to get basic necessities and doing activities. The negative effect of soil erosion for land productivity is decreasing water reserves, nutrition, organic substances and depth root. Soil erosion has decreased the ability of soil to hold up soft particle and organic substances carried over. A way to minimize the erosion effect is to apply the agroforestry system. Agroforestry is a sustainable conservation system for crop, trees and breed management based on the social-economic and ecological pattern.